Student Voter Resistance to Vote Buying in the 2024 General Election (Case Study of Students of the Department of Business Administration, Manado State Polytechnic) - Silvana, Grace Joice (International Journal Labs, 2024)
Vote buying is a form of money politics that is a serious threat to the integrity of the democratic process, especially among young voters, including students. This study aims to analyze student voter resistance to the practice of vote buying (money politics) in the 2024 election, with a case study of students of the Department of Business Administration of the Manado State Polytechnic. This study uses a quantitative survey mix method approach supported by group discussions and in-depth interviews. The findings show that student resistance to vote buying is partial and tends to be passive. As many as 50.5% of students stated that they rejected the offer of vote buying, but another 49.5% admitted to accepting. The rate of active rejection in the form of reporting of candidates who do vote buying is very low, with only 26.1% of students supporting reporting. This low active resistance is influenced by factors such as personal relationships with candidates, normalization of money politics in the surrounding environment, and uncertainty in attitudes as reflected in the average Likert scale score of 3.3 (neutral/hesitant). However, support for anti-vote buying campaigns is quite high, with an average scale of 3.9, and 86.9% of students agree to be a pioneer in rejecting the practice. This study highlights the gap between the moral attitude of students who reject vote buying and the concrete actions needed to stop the practice, as well as the importance of intervention through education and legal protection for whistleblowers.